(untitled) (GEON Journal (Management, Organizations and Business), 2019)
The patent is a complex legal tool that is part of the intellectual right, it is officially recognized to someone an invention and the rights that derive from it, we define the patent concept, we describe the Mexican system and we show the situation that the brands keep in Mexico. The theory shows that the economic benefits derived from the exploitation of the patent and the resulting inventions for public and private dissemination and use must be with benefits to society, which will raise the technical level of a country.